Technoeconomic Performance Analysis of Solar Tracking Methods for Roof-Type Solar Power Plants and Electric Vehicle Charging Stations - KIYAK, İSMAİL (HINDAWI LTD, 2021)
In building integrated photovoltaic (BIPV) solar energy projects, cost effectiveness, durability, and long-term reliability are among the criteria that should be taken into consideration as well as the gain in electricity generation efficiency. Also, in a study, it is stated that a dual-axis solar tracking system occupies approximately 100% more space than a single-axis system and 160% more than a fixed-angle system. It has been observed that most of the studies that are mounted on the building and include a tracking system are small-scale experimental studies. The aim of this article is to present a systematic analysis with a low investment cost, a low operating cost, and high reliability, in a real application especially for roof applications in buildings. Three buildings in the same location and with the same roof area were selected. Photovoltaic power plants with 23.68 kW power were installed; these panels had three types: fixed-angle, manually controlled, and single-axis solar tracking systems. The energy generation system is connected to the network with a double-sided meter, and there is a double-sided energy flow. The energy produced is used to meet the energy needs of the vehicle charging station and common areas of the buildings. Although the single-axis tracking system is 27.85% more efficient than other energy generation methods, the manually adjusted method has proven to have the shortest amortization time. The study also presents shading, which is a serious problem in large-scale roof projects, and the area covered by the module per unit watt produced.